2005
DOI: 10.1097/01.ccm.0000149852.32599.31
|View full text |Cite
|
Sign up to set email alerts
|

Invasive approaches to the diagnosis of ventilator-associated pneumonia: A meta-analysis

Abstract: Few trials have systematically examined the impact of diagnostic techniques on outcomes for patients suspected of suffering from ventilator-associated pneumonia. Invasive strategies do not alter mortality. Invasive approaches to ventilator-associated pneumonia affect antibiotic use and prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 27 publications
2
85
0
12
Order By: Relevance
“…A recent meta-analysis of the impact of invasive approaches on the diagnosis of VAP concluded that invasive lower airway sampling does not alter hospital mortality but consistently results in changes to the antibiotic regimen (182). In that study, the odds ratio for change in antibiotic management after invasive testing was 2.85 (95% CI, 1.45 to 5.59).…”
Section: Microbiologic Diagnosismentioning
confidence: 83%
See 1 more Smart Citation
“…A recent meta-analysis of the impact of invasive approaches on the diagnosis of VAP concluded that invasive lower airway sampling does not alter hospital mortality but consistently results in changes to the antibiotic regimen (182). In that study, the odds ratio for change in antibiotic management after invasive testing was 2.85 (95% CI, 1.45 to 5.59).…”
Section: Microbiologic Diagnosismentioning
confidence: 83%
“…The technique chosen in obtaining microbiologic data may indeed affect the clinical decision to de-escalate therapy. Heyland et al reported that the choice of bronchoscopic BAL and PSB resulted in increased physician confidence in the diagnosis and management of VAP; this resulted in a greater tendency to limit or discontinue antibiotics, an outcome that was echoed in a recent meta-analysis (79,182).…”
Section: Antibiotic Managementmentioning
confidence: 96%
“…(45) Alguns autores, (73) com menor número de pacientes e de maneira diversa ao estudo francês, compararam as duas estratégias; porém, utilizando culturas quantitativas em ambas, não tendo sido encontradas diferenças significativas entre os grupos quanto aos mesmos desfechos, fato que foi demonstrado em recente metanálise que incluiu os poucos estudos disponíveis a este respeito. (74) A utilização de culturas quantitativas em comparação com técnicas qualitativas parece proporcionar maior número de ajustes terapêuticos sem, contudo, influenciar diretamente na taxa de mortalidade, permanência na UTI e duração da VM. A precocidade e a adequação do tratamento são os principais determinantes dos bons resultados, mais do que a forma com que a PAVM é diagnosticada.…”
Section: Estudos Comparativos Entre As Técnicas Invasivas E Não Invasunclassified
“…Çalışmamızda; ETA kültür sonuçlarının VİP tanısındaki değerinin belirlenmesi amaç-lanmış ve pre-mortem alınan ETA örneklerinin kantitatif kültür sonuçlarıyla, post-mortem biyopsi örnekleri-nin bakteriyolojik ve patolojik inceleme sonuçları karşılaştırılmıştır. kob/mL ve üzerindeki üreme, "pozitif" kabul edilmiş ve uygun antibiyotik tedavisi başlanmıştır (7,8). Ateş yük-sekliği olan olgularda ayrıca, kan, idrar ve plevral sıvı örnekleri alınarak bakteriyolojik kültürleri yapılmıştır.…”
Section: Introductionunclassified